Analisis Efisiensi Sumber dan Penggunaan Modal Kerja pada PT Tri Anugrah Pratama Pekanbaru - Karni, Trisna Lodya; Wijaya, Errin Yani; ', Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the level of efficiency of PT Tri Anugrah Pratama Pekanbaru in managing the sources and uses of working capital to maintain the continuity of the company's operations and to analyze the contribution of the use of their own capital and bank capital to the development of corporate profits. This research was conducted in PT Tri Anugrah Pratama Pekanbaru is located at Jln Parit Indah Grand Sudirman Pekanbaru. In this study using secondary data in the form of: 1) The financial statements of the company for 5 years 2008-2013 and 2) Financial ratios. Analysis of the data used in this research is descriptive quantitative method. The study states that in order to measure the efficiency of the sources and uses of working capital, the working capital position of the company need to be analyzed by using the ratio of liquidity, solvency and profitability. Analysis of the reports and sources and uses, and analyzes the company's cash flow statement shows that the sources and uses of working capital has not been effective and efficient. PT Tri Anugrah Pratama are in a liquid state and insovable. More corporate capital derived from medium-term debt and long-term comparison of capital it self. This condition causes the contribution of working capital in the profit has decreased, it is because the company charges them interest on bank loans which is quite large.Keywords: Efficiency, Resource Management, Working Capital